Did aetiology matter in illness duration and complications in patients presenting in primary care with acute respiratory tract infections early in the COVID-19 pandemic: An observational study in nine countries - Venekamp, Roderick P.; Eijkemans, Marinus J.C.; Zuithoff, Nicolaas P.A.; Böhmer, Femke; Chlabicz, Slawomir; Colliers, Annelies; García-Sangenís, Ana; Malania, Lile; Pauer, Jozsef; Tomacinschii, Angela; Verheij, Theo J.; Goossens, Herman; et al. (The European journal of general practice, 2024)
Despite considerable research into COVID-19 sequelae, little is known about differences in illness duration and complications in patients presenting in primary care with symptoms of acute respiratory tract infections (RTI) that are and are not attributed to SARS-CoV-2 infection. To explore whether aetiology impacted course of illness and prediction of complications in patients presenting in primary care with symptoms of RTI early in the COVID-19 pandemic. Between April 2020-March 2021 general practitioners from nine European countries recruited consecutively contacting patients with RTI symptoms. At baseline, an oropharyngeal-nasal swab was obtained for aetiology determination using PCR after follow-up of 28 days. Time to self-reported recovery was analysed with Kaplan-Meier curves. Predictors (baseline variables of demographics, patient and disease characteristics) of a complicated course (composite of hospital admission and persisting signs/symptoms at 28 days follow-up) were explored with logistic regression modelling. Of 855 patients with RTI symptoms, 237 (27.7%) tested SARS-CoV-2 positive. The proportion not feeling fully recovered (15.6% vs 18.1%, = 0.39), reporting being extremely tired (9.7% vs 12.8%, = 0.21), and not having returned to usual daily activities (18.1% vs 14.4%, = 0.18) at day 28 were comparable between SARS-CoV-2 positive ( = 237) and negative ( = 618) groups. However, among those feeling fully recovered (SARS-CoV-2 positive: 200 patients, SARS-CoV-2 negative: 506 patients), time to full recovery was significantly longer in SARS-CoV-2 patients (10.6 vs 7.7 days, < 0.001). We found no evidence that predictors of a complicated course differed between groups ( = 0.07). Early in the pandemic, the proportion of patients not feeling fully recovered by 28 days was similar between SARS-CoV-2 positive and negative patients presenting in primary care with RTI symptoms, but it took somewhat longer for SARS-CoV-2 patients to feel fully recovered. More research is needed on predictors of a complicated course in RTI.